PENGEMBANGAN MEDIA VIDEO ANIMASI PENCEGAHAN COVID-19 PADA REMAJA (Politeknik Kesehatan Kemenkes Bandung, 2021)
A coronavirus is a group of new types of viruses that can cause respiratory tract infections in adolescents. Covid-19 cases based on age in West Bandung Regency until May 2021 are dominated by teenagers. Promotive and preventive efforts that can be done are by providing education through animated video media. In line with previous research, the provision of animated video information is effective in increasing students' knowledge. This study uses a mixed-method approach with an exploratory sequential mixed methods design, starting with qualitative data collection followed by quantitative data collection. A probability sampling method with a simple random sampling technique was used in determining the 52 samples of participants. In collecting qualitative data, an exploration of media needs was carried out with phenomenological studies and prototyping, in quantitative data collection, a media feasibility test was carried out on 1 media expert by getting a percentage score of 100%